POTASSIUM FORMS FOR MAIN SOIL ORDERS IN THE NORTH OF IRAQ - ISMAIL, HAJEEN KHALIL; MEHMEDANY , LAZKEEN AHMED MERWEEN; MOHAMMED, HOGIR SALIM (Journal of Duhok University, 2021)
Fifteen soil samples were collected from five locations in the North of Iraq from three surface genetic horizons for the five locations [Semeel (Vertisols), Imerik (Aridisols), Gerderash (Inceptisols), Perdi (Aridisols) and Wermawa (Mollisols)] to study the forms of potassium and its distribution with the depth. All studied soils are calcareous and non-saline soils contain low organic matter. The studied forms of K in the surface horizons of the studied soils (soluble, exchangeable, available, non-exchangeable, mineral and total potassium) were ranged between (12 – 40, 82 – 229, 97 – 246, 656 – 3800, 462 – 2933 and 1200 – 5400) mg kg-1 respectively, while in the intermediate (A and A1) soil horizons were (5 –26,  67 – 214 ,  72 –  216 ,  676 – 3040 , 709 – 2048  and  1700 – 5200) mg kg-1 respectively and in the third horizon of studied soils were (4 – 14 ,  68 – 191, 70 – 186 ,  345 – 3232 ,  419 – 4516  and 1700 – 5800) mg kg-1 respectively, this illustrates the amount of soluble, exchangeable, available (soluble + exchangeable), non-exchangeable decreases with the depth. The constituted percent of the soluble, exchangeable; available; nonexchangeable and mineral potassium from total-K in all pedons equal to 0.469; 4.185 ; (4.538); 52.141 and 43.318 respectively.Correlation study illustrates positively and significantly correlated between total potassium with exchangeable, available, non-exchangeable, mineral, while positively and significant relation demonstrate between exchangeable, available, non-exchangeable with silt content in the soils, but positively relation found between soluble potassium with pH and negatively to EC. The high amount of soluble K found in Perdi pedon (Aridisols) but higher amount of the exchangeable, non- exchangeable, available and total-K demonstrate in Imerik pedon (Aridisols) while large amount of mineral-K shown in Gerderash pedon (Inceptisols)